Perbandingan TextRank Berbasis TF-IDF dan Word2Vec dalam Peringkasan Teks Berita Bahasa Indonesia - Yohannes Christian Gurning; Samuel Cristian Saragih; Yuyun Yusnida Lase; Julham Julham (LKP KARYA PRIMA KURSUS, 2025)
Automatic text summarization has become an essential solution for processing massive textual information, particularly in lengthy news articles. This study compares two variants of the TextRank algorithm using different weighting schemes: TF-IDF and Word2Vec, for summarizing Indonesian news texts. The dataset comprises 160 news articles from Kompas.com, which underwent preprocessing. Evaluation was conducted using ROUGE metrics (ROUGE-1, ROUGE-2, ROUGE-L), manual readability assessment, and execution runtime. The results indicate that TextRank with Word2Vec outperforms TF-IDF in both ROUGE scores (ROUGE-1 F1: 0.7033 vs 0.6454) and processing speed. These findings suggest that incorporating semantic representations into graph-based algorithms like TextRank significantly improves summary quality and runtime efficiency.